Clonal haematopoiesis and COVID‐19: A possible deadly liaison. (8th June 2020) - Shivarov, Velizar; Ivanova, Milena
Abstract: We provide evidence for a linear correlation between the frequency of clonal haematopoiesis and COVID‐19 mortality rate. We discuss the mechanistic explanations for this association mediated by a pathological inflammatory response. Our hypothesis can be tested in COVID‐19‐infected patients and eventually lead to new approaches to risk stratification and therapy.